Escuela de Danza - Ávila Aguilar, Marta (Editorial Universidad Nacional (EUNA), 2014)
This book aims to fill a gap in the documentation on the contribution made by the Art Schools of the Universidad Nacional, grouped in the Center for Research, Teaching and Artistic Extension (CIDEA), in the context of the celebration of 40 years of creation of this house of studies. This work highlights the academics who are in exercise and have deserved recognition for their trajectory, administrative periods of merit; deceased professors, as well as some retired teachers are also protagonists.